Fatal cocaine intoxication in a body packer - Brajković, Gordana; Babić, Gordana; Jović Stošić, Jasmina; Tomašević, Gordana; Rančić, Dragana; Kilibarda, Vesna (Vojnosanitetski pregled, 2017)
Introduction. ‘Body packer’ syndrome with severe intoxication or sudden death may happen in persons who smuggle drugs in their body cavities. In case of lethal outcome when carrying cocaine, it is important, but sometimes difficult to determine whether death was due to intoxication or due to other causes. Therefore, it is necessary not only to quantify cocaine and its metabolites in biological material, but also based on their distribution in body fluids and tissues to conclude whether it is acute intoxication. We described a well-documented case of fatal poisoning in a body packer and post mortem distribution of the drug in biological samples. Case report. A 26-year-old man was brought to hospital with no vital signs. Resuscitation measures started at once, but with no success. Autopsy revealed 66 packets of cocaine in his digestive tract, one of which was ruptured. Hyperemia of the most of all internal organs and pulmonary and brain edema were found. High concentrations of cocaine, its metabolites benzoylecgonine and ecgonine methyl ester, as well as cocaine adulteration levamisole were proven in the post mortem blood and tissues by liquid chromatography-mass spectrometry (LC-MC) method with selective-ion monitoring. Conclusion. The ratio of cocaine and its metabolites concentrations in the brain and blood obtained by LC-MS method can be used for forensic confirmation of acute intoxication with cocaine.